The high-kilted muse : Peter Buchan and his Secret songs of silence - Buchan, Peter, 1790-1854; Shoolbraid, Murray (University Press of Mississippi ; in association with the Elphinstone Institute, University of Aberdeen, Scotland, 2010)
In 1832 the Scottish ballad collector Peter Buchan of Peterhead, Aberdeenshire, presented an anthology of risqué? and convivial songs and ballads to a Highland laird. When Professor Francis James Child of Harvard was preparing his magisterial edition of The English and Scottish Popular Ballads, he made enquiries about it, but it was not made available in time to be considered for his work. On his death it was presented to the Child Memorial Library at Harvard. Because of its unseemly materials, the manuscript has languished there ever since, unprinted, though referred to now and again, and a.